Challenges Faced By Girl Child Aged Between 9-18 Years In Menstrual Hygiene In Schools. A Cross-Sectional Study of Ogur Sub-County, Lira District Uganda. - Aluma, Franco; Ongom, Ambrose (Student’s Journal of Health Research Africa, 2021)
Background: Menstruation is a naturally occurring physiological phenomenon in adolescent girls and pre-menopausal women. menstrual hygiene management ( MHM) is the practice that involves women and adolescent girls using clean menstrual management materials to absorb or collect blood that can be changed in privacy as often as necessary for the duration of the menstruation period, using soap and water for washing the body as required and access to the facilities off used menstrual management materials. Method: The research study employed quantitative and simple random sampling techniques from various strata and was carried out for one week from 17th November 2020 to 24th November 2020. A total of 30 pupils were selected, Data was collected on a data collection tool and information was presented using descriptive statics in form of tables, pie charts, and graphs. Results: The overall results showed in the age group between 14-16 years which had 10(52.6%) the least which had 1(5.2%), of the girls who faced challenges in menstrual hygiene management during school period. Conclusion: The high percentage of girls who faced challenges in menstrual hygiene management in school was due unavailability of menstrual hygiene facilities in Ogur primary school and the lack of continuous menstrual health education among girls. Recommendation: There is a need for menstrual health education among girl children, and provision of required menstrual hygiene facilities at school, public awareness on health-seeking behaviors and hygiene to reduce infections on girl children during their menstruation period. I also recommend further studies to be done in this area to evaluate the current challenges of poor menstrual hygiene among girl children in school.